Leading Article - Mahattanatawee, Kanjana (Journal of Food Technology, Siam University, 2021)
Fundamentals of science: physics, biology and chemistry, lead to applications in everyday life. Food product development is one of the said sciences to meet the needs of consumers. This can be seen from research papers in the Journal of Food Technology, Volume 16, Issue 2, which presents the efficiency of the extraction technique using ultrasound, effect of spray drying and freeze drying on the amount of antioxidant compounds, and the development of shallot tea with antioxidant properties. There is also research to produce seasoning sauce from local vegetables to add value and become an alternative seasoning sauce for health-conscious consumers. The production of Instant pork knuckle is convenient for modern life that is popularly heated or cooked by microwave. Furthermore, the production of biofilm containing antimicrobial plant extract is applied in food during packaging storage. Food Technology Journal of Siam University has published with the aim of disseminating research results and services to society. Every article has been reviewed by experts in related fields from many educational institutions. The editorial team hopes that readers will gain useful knowledge in academics and can also be used as a further reference.